2017
DOI: 10.1080/15569527.2017.1322098
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial changes in long-term cannabinoid users

Abstract: A significant decrease in CD was found in cannabinoid users compared the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The possible inhibition of p38 MAP kinase may also be a possible theory for the hyperopic shift [10][11][12]. Effects of cannabinoids on the anterior segment of the eye are also multiplex, and some studies indicate decreased corneal endothelial density [13]. Further studies will be needed to assert the findings from this isolated presentation of the case to better understand the role of CBD oil in refractive errors of the eye, especially in a diabetic condition.…”
Section: Discussionmentioning
confidence: 96%
“…The possible inhibition of p38 MAP kinase may also be a possible theory for the hyperopic shift [10][11][12]. Effects of cannabinoids on the anterior segment of the eye are also multiplex, and some studies indicate decreased corneal endothelial density [13]. Further studies will be needed to assert the findings from this isolated presentation of the case to better understand the role of CBD oil in refractive errors of the eye, especially in a diabetic condition.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it should be noted that there are challenges in formulation of these very lipophilic compounds. Their use may, in fact, either not be able to penetrate the target organs or result in dose-dependent ocular and systemic toxicity with chronic use [73,74]. Thus, future research should explore novel cannabinoid drug combinations, appropriate routes of local delivery and evaluate both acute and chronic dosing in representative models of ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system (ECS) has also been found to play a role in lowering intraocular pressure, making cannabis a potential therapeutic agent in managing glaucoma. However, its side effects, i.e., tolerance and accompanying psycho-active influence have largely limited this use [64,65]. A mice study has shown topical application of cannabis extract to reduce corneal hyperalgesia and neutrophil infiltration resulting from superficial chemical injury of corneal epithelium [66].…”
Section: Ophthalmologicalmentioning
confidence: 99%